INLAND FISHERIES SCIENCE: A LIMNOLOGIST’S PERSPECTIVE* - GOPAL, BRIJ (Journal of the Inland Fisheries Society of India, 2021)
This paper traces the historical developments in fisheries science and limnology, which started at about the same time. Globally, as also in India, fisheries science was rooted in limnology - the science of inland water ecosystems. The two disciplines drifted apart as fisheries focused more on aquaculture for increased yields and limnology (particularly in India) got obsessed with physico-chemical water quality and plankton populations. However, in recent years, the two disciplines have found a common ground in areas such as environmental flows, biomanipulation, catchment influences on aquatic systems and the ecosystem services and biodiversity of inland waters. The fisheries science will grow only with the ecosystem-level studies of inland waters.Key words: Aquatic biodiversity, biomanipulation, ecosystem services, water pollution.